APPLICATION AND REFLECTION OF PHILOSOPHY ON ELEMENTARY SCHOOL MATHEMATICS CONTENT - Rina Dyah Rahmawati; Sugiman Sugiman; Taufik Muhtarom; Mohammad Archi Maulyda (Program Studi PGSD Universitas Flores, 2025)
The current disruptive era demands many changes in various areas of life. Likewise, the technological transformation has significant unavoidable consequences. This is where it is necessary to consider a strong foundation for students from the elementary level. This article examines the application and reflection of philosophy on the content of elementary school mathematics in Indonesia. The background of this study is the need for an era where there is a need for constructive mathematics learning from an early age towards learning the Industrial Revolution 4.0. The purpose of this study is to identify (1) the nature of symptoms or objects of application and reflection of philosophy in elementary mathematics (ontological reasons), (2) how to obtain or manage symptoms or objects (epistemological reasons), (3) the benefits of symptoms or objects (axiological reasons), and two-way understanding of phenomena and objects (hermeneutics). Data is obtained based on relevant sources such as journal articles, books, and previous research results supported by qualitative analysis. The results of this study indicate the need to reveal the application and reflection of philosophy in low-grade mathematics content through the ontology of mathematics, epistemology, axiology, and hermeneutics.